2022
DOI: 10.1007/s00296-022-05233-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic growth in adult patients with systemic lupus erythematosus: a cross-sectional study in China

Abstract: This cross-sectional study aims to evaluate the post-traumatic growth (PTG) level and explores its predictors among adult patients with SLE in China. From April 2020 to April 2021, 135 hospitalized adult SLE patients completed the questionnaire including sociodemographic and disease-related data, Post-traumatic Growth Inventory (PTGI), Medical Coping Modes Questionnaire (MCMQ), Social Support Rating Scale (SSRS), Pittsburgh Sleep Quality Index (PSQI), Hospital Anxiety and Depression Scale (HADS), and Self-Perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…47 To improve the QOL of individuals with SLE, healthcare professionals and family members should focus on factors closely associated with QOL and implement appropriate interventions. 48,46 This study found a positive correlation between social support and QOL in SLE patients. 49 SLE is a long-term condition, and with advancements in modern medicine, patients now have longer survival periods, thereby requiring higher levels of social support.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…47 To improve the QOL of individuals with SLE, healthcare professionals and family members should focus on factors closely associated with QOL and implement appropriate interventions. 48,46 This study found a positive correlation between social support and QOL in SLE patients. 49 SLE is a long-term condition, and with advancements in modern medicine, patients now have longer survival periods, thereby requiring higher levels of social support.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, this study demonstrates a positive correlation between post-traumatic growth and QOL in SLE patients. 46 Patients with SLE may embrace the trauma caused by the disease through positive coping mechanisms, leading to personal growth, self-acceptance, and the discovery of meaningful aspects in other areas of life, fostering a more optimistic outlook. 47 To improve the QOL of individuals with SLE, healthcare professionals and family members should focus on factors closely associated with QOL and implement appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%